Opting Out: Examining Teacherâs Beliefs When Faced With Core Reading Programs - Tynisha D. Meidl (Arizona State University, 2013)
This qualitative study focused on how teachers in a small, urban elementary school in Pennsylvania negotiate their beliefs and instructional delivery the classroom. In the area of literacy instruction, there has been an increased reliance on Core-reading programs in elementary school. Classroom teachers, caught in the middle, are charged with the responsibility to raise test scores, plan curriculum, motivate students, and provide a welcoming learning environment for all students. In this article, teachers' beliefs about meeting the needs of urban students amidst NCLB were explored, in relation to curriculum planning. A case study approach guided this research, using interviews, observations, and document analysis. Data from participant statements and researcher observations, illuminate the reasons why teachers "opted-out" of having a sense of fidelity towards the mandated curriculum. According to the researcher opting-out was a means to equalize the discord between meeting student academic needs while adhering to the mandated curriculum and pacing guide.